The phylogenomics and evolutionary dynamics of the organellar genomes in carnivorous Utricularia and Genlisea species (Lentibulariaceae) - Silva, Saura R; Miranda, Vitor F O; Michael, Todd P; Płachno, Bartosz J; Matos, Ramon G; Adamec, Lubomir; Pond, Sergei L K; Lucaci, Alexander G; Pinheiro, Daniel G; Varani, Alessandro M (Molecular phylogenetics and evolution, 2023)
Utricularia and Genlisea are highly specialized carnivorous plants whose phylogenetic history has been poorly explored using phylogenomic methods. Additional sampling and genomic data are needed to advance our phylogenetic and taxonomic knowledge of this group of plants. Within a comparative framework, we present a characterization of plastome (PT) and mitochondrial (MT) genes of 26 Utricularia and six Genlisea species, with representatives of all subgenera and growth habits. All PT genomes maintain similar gene content, showing minor variation across the genes located between the PT junctions. One exception is a major variation related to different patterns in the presence and absence of ndh genes in the small single copy region, which appears to follow the phylogenetic history of the species rather than their lifestyle. All MT genomes exhibit similar gene content, with most differences related to a lineage-specific pseudogenes. We find evidence for episodic positive diversifying selection in PT and for most of the Utricularia MT genes that may be related to the current hypothesis that bladderworts' nuclear DNA is under constant ROS oxidative DNA damage and unusual DNA repair mechanisms, or even low fidelity polymerase that bypass lesions which could also be affecting the organellar genomes. Finally, both PT and MT phylogenetic trees were well resolved and highly supported, providing a congruent phylogenomic hypothesis for Utricularia and Genlisea clade given the study sampling.
Keywords: Lamiales; Molecular evolution; biologická evoluce; hluchavkotvaré; Biological Evolution; Mitogenome; Ndh evolution; Carnivorous plants; Phylogeny; fylogeneze; Adaptation; Magnoliopsida; Plastome